SISTEM INFORMASI MANAJEMEN RUSUNAWA UNIKI BERBASIS WEB - Chaeroen Niesa (SADIDA, 2023)
In this day and age technology is needed along with meeting the needs itself. Information technology is one of the technologies that is currently developing rapidly. With advances in information technology, access to available data or information can take place quickly, efficiently, and accurately (Arfianto and Nugrahanti 2018). The goal is to produce something better, faster and more accurate, especially regarding information systems in the management of student flats (RUSUNAWA) especially at the Indonesian National Islamic University (UNIKI) Bireuen Regency. At this time, RUSUNAWA at the Universitas Islam Kebangsaan Indonesia ( UNIKI) Bireuen in the management of RUSUNAWA still uses a manual system, namely by registering students staying at the RUSUNAWA. This system is considered inefficient considering the rapid increase in the number of students who will occupy the RUSUNAWA. This chapter discusses the problems that will be created and the analysis of the old system, analysis of the new system, context diagrams, DFD, databases, ERD, interface design and output regarding the problems that will be developed in accordance with the program that will be designed, the problem is that it is not yet There is a management system at the RUSUNAWA UNIKI Bireuen and staff at the RUSUNAWA still use a manual system in the form of a record book. RUSUNAWA is an abbreviation of flats in the form of a multi-storey building that was built in a campus environment at the Indonesian National Islamic University (UNIKI). outside the area, and this is a place to stay that has an integrated toilet and kitchen, by paying rent every month, year and day to the owner. With the existence of a database-based information system, the RUSUNAWA Management Information System, the Indonesian National Islamic University. Can be done quickly, precisely and accurately. A good data information system will facilitate the management and processing so that it can improve the performance of employees at the RUSUNAWA of the Indonesian National Islamic University in particular. System design using MySQL-based web programming language makes it easier to design as well as to the final result (output) and more easily understood by users.